C.1 - Kennan, George F. (New York, 1964)
THE LECTURES embodied in this book were written and delivered shortly after my return to this country from some two and a half years of service on behalf of the United States Government in one of the countries of Eastern Europe. This service involved a number of personal encounters, and a good deal of correspondence, with people in the opinion-forming echelons of our public life, devoted to the effort to find understanding for an approach to the problems of the Communist orbit which would look care fully at each of the countries of that area as it exists today, and which would try to identify the hopeful forces and currents of opinion there and then shape policy with a view to encouraging these forces and helping them to become effective in the interests of a more relaxed and safer international life.
Keywords: Communist countries